The Effect of Water Games on Gross Motor Skills in Early Childhood (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to investigate the impact of water play on the motor skills of young children. The research method used was an experiment with a one-group pretest-posttest design. The subjects of the study were 7 children aged 4–7 years, selected using a purposive sampling technique. The measurement instrument used was the Movement Assessment Battery for Children (MABC), which included tests of throwing as far as possible, running obstacles, and jumping without a run-up. The treatment, in the form of a water play program, was conducted over 6 meetings, each lasting 60 minutes. Data analysis was conducted using a paired sample t-test at a significance level of 0.05. The results showed an increase in the average score from 5.14 in the pretest to 8.00 in the posttest. The t-test yielded a significance value of 0.000 (p < 0.05), indicating a highly significant difference between the before and after treatment groups. Thus, water play has been proven to have a positive effect on improving the motor skills of early childhood. This activity can be recommended as an alternative method of physical learning that is fun and effective in early childhood education.